Penerapan Bibliotherapy sebagai Intervensi dalam Keperawatan Anak - Indah, Desi Puspita; Fitri, Siti Yuyun Rahayu; Rukmasari, Ema Arum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the effectiveness of bibliotherapy on children's emotional and psychological problems as part of nursing interventions and to identify factors that can influence the success of its implementation. This research method uses an integrative review approach. The results of the study obtained 10 articles that showed the influence of bibliotherapy as a nursing intervention in overcoming children's psychological and emotional problems, such as reducing anxiety, overcoming stress, and improving self-concept in children who experience certain medical conditions both in hospitals and other service facilities such as SLB or orphanages. Conclusion Bibliotherapy can be applied as one of the interventions in child nursing to reduce psychological problems in children, especially those who are hospitalized or who experience special conditions such as mental retardation or loss of parents. Keywords: Children, Bibliotherapy, Nursing Interventions